Exploring the dynamic role and cultural meaning of the ‘Berasan’ in Rejang traditional weddings in Bengkulu Province - Didi Yulistio; Sarwit Sarwono; Reko Serasi; Nova Efrianti (UNIB Press, 2025)
The 'Berasan' tradition in Rejang traditional weddings in Bengkulu Province shows significant dynamics in its development. Because it is a cultural system of community life, this tradition is important to understand so that it is widely known and studied in depth by experts, both within and outside Bengkulu Province. This study aims to describe the dynamics of the 'berasan' culture related to its history, system, ceremonial structure, meaning, and shifting patterns of variation in Rejang traditional weddings in Bengkulu Province. This study uses an ethnographic survey method and a qualitative approach. Data collection from informants (who meet the requirements for the study of oral traditions) through interviews and documentation in the form of words, sentences, symbolic actions, and objects or equipment used as well as secondary data, such as texts, traditional manuscripts, and videos of the 'Berasan' procession. Data analysis techniques are carried out through the stages of listening, viewing, and recording as well as transcribing, analyzing, and interpreting data according to the problem and drawing conclusions. The results of the research